2023
DOI: 10.3390/ijms241310742
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Sulfide in Regulation of Cell Death following Neurotrauma and Related Neurodegenerative and Psychiatric Diseases

Abstract: Injuries of the central (CNS) and peripheral nervous system (PNS) are a serious problem of the modern healthcare system. The situation is complicated by the lack of clinically effective neuroprotective drugs that can protect damaged neurons and glial cells from death. In addition, people who have undergone neurotrauma often develop mental disorders and neurodegenerative diseases that worsen the quality of life up to severe disability and death. Hydrogen sulfide (H2S) is a gaseous signaling molecule that perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 289 publications
0
4
0
Order By: Relevance
“…H 2 S’s multifaceted role in modulating lipid peroxidation and cellular redox balance positions it as a potent inhibitor of ferroptosis. Its capacity to scavenge lipid peroxides and ROS and promote the expression of antioxidant enzymes, such as glutathione peroxidase 4 (GPX4), highlights its regulatory prowess in thwarting ferroptotic processes [ 10 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 S’s multifaceted role in modulating lipid peroxidation and cellular redox balance positions it as a potent inhibitor of ferroptosis. Its capacity to scavenge lipid peroxides and ROS and promote the expression of antioxidant enzymes, such as glutathione peroxidase 4 (GPX4), highlights its regulatory prowess in thwarting ferroptotic processes [ 10 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also exerts anti-inflammatory effects by inhibiting NF-κB activation. Additionally, H 2 S displays cytoprotective effects by scavenging ROS and enhancing antioxidant enzyme activities, mitigating oxidative stress and cellular damage [ 10 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that H 2 S, similar to CO and NO, plays an important role in anti-inflammatory and anti-apoptotic effects in oxidative stress reactions [ 11 , 12 ]. H 2 S and its donor, sodium hydrosulfide (NaHS), have protective effects on the spinal cord and related diseases [ 13 , 14 ]. H 2 S is also effective in the treatment of SCI-induced complications, such as osteoporosis [ 15 ].…”
Section: Intervention and Regulatory Effects Of Hydrogen Sulfide On Scimentioning
confidence: 99%
“…Typically, in neurotrauma, H 2 S levels tend to decrease, which adversely affects the survival of neurons and glial cells. H 2 S mainly has a neuroprotective effect by reducing oxidative stress, activating antioxidant enzymes, and reducing the level of neuroinflammation and apoptosis [9][10][11]. Of particular interest are the subtle H 2 S-dependent mechanisms of regulation of proapoptotic signaling through direct interaction with target proapoptotic proteins through S-sulfhydration or persulfhydration of cysteine residues, inhibition or activation of various signaling pathways, etc.…”
Section: Introductionmentioning
confidence: 99%